Tri-allelic pattern of short tandem repeats identifies the murderer among identical twins and suggests an embryonic mutational origin. (May 2015) - Wang, Li-Feng; Yang, Ying; Zhang, Xiao-Nan; Quan, Xiao-Liang; Wu, Yuan-Ming
Highlights: The real criminal from monozygotic twins was "unluckily" identified through the traditional STR test by the accidental emerge of a tri-allelic pattern. STR as personal genetic marker could mutate pass generations. Loop containing false priming induced STR repeat length variation occurs in cell mitosis, which is after embryonic zygote formation and during the early development of the individual after the division of the blastocyte. The genotypes of parent–child mismatches, aberrant di-allelic patterns, and type 1 or 2 tri-allelic patterns should be considered as independent, but interconnected forms of STR mutation. Abstract: Monozygotic twins can be co-identified by genotyping of short tandem repeats (STRs); however, for distinguishing them, STR genotyping is ineffective, especially in the case of murder. Here, a rarely occurring tri-allelic pattern in the vWA locus (16, 18, 19) was identified only in the DNA of one identical twin, which could help to exonerate the innocent twin in a murder charge. This mutation was defined as primary through genotyping of the family and could be detected in blood, buccal and semen samples from the individual; however, two alternative allele-balanced di-allelic patterns (16, 18 or 16, 19) were detected in hair root sheath cells. Such a kind of segregation indicates a one-step mutation occurs in cell mitosis, which is after embryonic zygote formation and during the early development of the individual after the division of the blastocyte. Sequencing revealed the insertion between the allele 18 and 19 is a repeat unit of TAGA/TCTA (plus/minus strand), which belongs to "AGAT/ATCT"-based core repeats identified from all tri-allelic pattern reports recorded in the STR base and a detailed model was proposed for STR repeat length variation caused by false priming during DNA synthesis. Our model illustrates the possible origination of allele-balanced and unbalanced tri-allelic pattern, clarifies that the genotypes of parent–child mismatches, aberrant di-allelic patterns, and type 1 or 2 tri-allelic patterns should be considered as independent, but interconnected forms of STR mutation.